Traceability of the WBCO Standard Attenuator by Comparing With A Inductive Voltage Dividers - Krraoui Houssemeddine; Lerat Jean-Marie (EPJ Web of Conferences)
A measurement system for the traceability of attenuation of a Waveguide Below Cut-Off attenuator standard (WBCO) is presented. This system consists of calibrating a lock-in amplifier at 10 kHz by frequency substitution using a WBCO at 30 MHz and a Inductive Voltage Dividers IVD as primary standards at 10 kHz. The new systems allows the establishement of a new traceability scheme at LNE, the French National Metrology Institue, The paper hereby describes the measurement method, and details the associated measurement model. Then a validation method is presented and the results are discussed. .